HOW DO CORPORATE SUSTAINABILITY AND PANDEMIC AFFECT CASH HOLDINGS IN MUSLIM COUNTRIES? - Tekin, Hasan; Burgazoglu, Huseyin (Bank Indonesia, 2022)
We investigate how corporate sustainability (Environmental, Social, and Governance-ESG) influences cash holdings of non-financial firms in Muslim countries from 2003 to 2021. Using panel models, we find that firms with lower ESG hold more cash over the entire period, which aligns with the agency and precautionary motives of cash holdings. We also note that the negative relation between ESG and cash holding is not affected by the COVID-19 pandemic. Looking at individual countries in the sample, we note a positive relation between ESG and cash balances for Saudi Arabia. Meanwhile, similar to the full sample, their relation is negative for firms from Malaysia and Turkiye. Finally, the ESG and cash policies of firms in different industries tend to vary. Overall, firms in Muslim countries use cash holdings as a substitute for corporate sustainability without any changes in the COVID era. Acknowledgment The authors would like to thank Bank Indonesia Institute, Bank Indonesia, for the funding that made this study possible.